Hot consolidated all-PP composites from textile fabrics composed of isotactic PP filaments with different degrees of orientation (eXPRESS Polymer Letters)
Self-reinforced polypropylene composites (SRPPC) were hot pressed from textile layers (carded mat, knitted fabrics) at three different temperatures (160, 165 and 170°C) by setting a constant pressure (6 MPa) and constant holding time (2 min). Both textiles consist of two kinds of isotactic polypropylene (iPP) fibers differing in their orientation. In these compositions the highly oriented iPP works as reinforcement and the less oriented one fulfills the role of the matrix after hot consolidation. Two textile assemblies, viz. carded (also needle punched) mats and knitted fabrics were hot pressed; and the properties of the resultant SRPPC plates were investigated under tensile and falling weight impact conditions. The microstructure of the SRPPC was analyzed by light microscopy using polished sections and by SEM using cut surfaces.